Effect of Vitis vinifera Seed Extract on some of the Reproductive Parameters in Adult Male Rat - MR Afzalzadeh; AA Papahn; A Amirzargar; M Kazemi Varnamkhasti; H Ganjali; E Gharib mombeni (Institue of Medicinal Plants, ACECR, 2014)
Background: Grape seed extract (GSE) (Vitis vinifera L., Vitacease) has been reported to have many biological and pharmacological activities such as antioxidative affects also it used traditionally to treat constipation, gastritis and etc. On the other hand, it said that used of GSE can reduced sperms. Objective: The present study aimed to investigate the effect of decrease and immobilization grape seed hydroalcoholic extract (GSHE) on sperm parameters in adult male rat. Methods: In this study eighteen sexually mature male Wistar rats (5 - 6 month old) weighing between 250 - 300 g were used randomly and divided into three groups of 6 rats each. Crushed grape seeds were extracted in ethanol, and the two doses of it (250 and 500 mg/kg) was administered into two experimental groups, so the control group only received 1ml normal saline by gavage for 42 days consecutively. 24h after last dosage, all the animals were anesthetized. Then, their couda epididymis and testes were isolated and they were put into normal saline separately after that, sperm motility, total sperm and daily sperm production were measured. Results: The results revealed a significant decrease in cauda epididymal, testicular sperm counts and daily sperm production, also percent of sperm-progressive motility in comparison with control group (p≤ 0.05). Conclusion: Our results of this study show that GSHE causes significant decrease in the sperm motility, count and daily sperm production without any change in body and accessory sex glands weight.